The Role of Bacterial-Derived Aromatic Amino Acids Metabolites Relevant in Autism Spectrum Disorders: A Comprehensive Review - Zheng, Yuanpeng; Bek, Marie K.; Prince, Naika Z.; Peralta Marzal, Lucia N.; Garssen, Johan; Perez Pardo, Paula; Kraneveld, Aletta D. (Frontiers in Neuroscience, 2021)
In recent years, the idea of the gut microbiota being involved in the pathogenesis of autism spectrum disorders (ASDs) has attracted attention through numerous studies. Many of these studies report microbial dysregulation in the gut and faeces of autistic patients and in ASD animal models. The host microbiota plays a large role in metabolism of ingested foods, and through the production of a range of metabolites it may be involved in neurodevelopmental disorders such as ASD. Two specific microbiota-derived host metabolites, p-cresol sulfate and 4-ethylphenyl sulfate, have been associated with ASD in both patients and animal models. These metabolites originate from bacterially produced p-cresol and 4-ethylphenol, respectively. P-cresol and 4-ethylphenol are produced through aromatic amino acid fermentation by a range of commensal bacteria, most notably bacteria from the Clostridium genus, which are among the dysregulated bacteria frequently detected in ASD patients. Once produced, these metabolites are suggested to enter the bloodstream, pass the blood-brain-barrier and affect microglial cells in the central nervous system, possibly affecting processes like neuroinflammation and microglial phagocytosis. This review describes the current knowledge of microbial dysbiosis in ASD and elaborates on the relevance and synthesis pathways of two specific ASD-associated metabolites that may form a link between the microbiome and the brain in autism. While the two discussed metabolites are promising candidates for biomarkers and (nutritional) intervention targets, more research into the role of these metabolites in ASD is required to causally connect these metabolites to ASD pathophysiology.